COVID-19 pandemic: Impact and rapid reaction of urology (2020)
The COVID-19 pandemic caused by the SARS-CoV-2 virus has caused tens of thousands of deaths in Spain and has managed to breakdown the healthcare system hospitals in the Community of Madrid, largely due to its tendency to cause severe pneumonia, requiring ventilatory support. This fact has caused our center to collapse, with 130% of its beds occupied by COVID-19 patients, thus causing the absolute cessation of activity of the urology service, the practical disappearance of resident training programs, and the incorporation of a good part of the urology staff into the group of medical personnel attending these patients. In order to recover from this extraordinary level of suspended activity, we will be obliged to prioritize pathologies based on purely clinical criteria, for which tables including the relevance of each pathology within each area of urology are being proposed. Technology tools such as online training courses or surgical simulators may be convenient for the necessary reestablishment of resident education.